On UL-DL Imbalance Mitigation for HSPA Heterogeneous Network - Liu Liu; Yongyu Chang; Rongqian Qin; Chi Zhang; Dacheng Yang (IEEE Vehicular Technology Conference, 2014)
Heterogeneous network (HetNet) which contains different transmission power NodeBs has been researched extensively earlier in LTE system. Owing to the great improvement achieved by HetNet, HSPA HetNet is currently being standardized by 3GPP working group. In co-channel HSPA HetNet (CHH), Uplink-Downlink (UL-DL) imbalance caused by the hugely different power from different types of transmission nodes is a key problem leading to many undesirable conditions such as unbalanced load and severe interference. The main contribution of this paper is to propose an adaptive range expansion (ARE) mechanism to mitigate the UL-DL imbalance in CHH. Our scheme tries to adaptively calibrate the parameter of range expansion (RE) by means of introducing an Imb value and using it as a reference to reflect the imbalance condition in the system. Simulation results will show the advantages of our proposed scheme.